2006
DOI: 10.1051/forest:2006031
|View full text |Cite
|
Sign up to set email alerts
|

ISSR and AFLP identification and genetic relationships of Chinese elite accessions from the genusPopulus

Abstract: -Inter-simple sequence repeat polymorphism (ISSR) and amplified fragment length polymorphism (AFLP) analysis techniques were used in this study for the genetic fingerprinting and identification of 28 important Chinese poplar accessions. After fingerprinting, the genetic relationships among the accessions were determined. Each of three ISSR primers and four AFLP primer pairs produced fingerprint profiles that were unique to each of the accessions studied, and thus could be used solely for their identification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Lu et al (2006) used ISSR primers to study seven natural populations of Populus cathayana (161 genotypes) and reported 98.7% polymorphism. In another study, ISSR marker polymorphism was a little lower (84%) among 28 genotypes of various Populus species (Jianming et al, 2006). These various studies confirm the high genetic diversity of Salix and Populus species.…”
Section: Discussionsupporting
confidence: 58%
“…Lu et al (2006) used ISSR primers to study seven natural populations of Populus cathayana (161 genotypes) and reported 98.7% polymorphism. In another study, ISSR marker polymorphism was a little lower (84%) among 28 genotypes of various Populus species (Jianming et al, 2006). These various studies confirm the high genetic diversity of Salix and Populus species.…”
Section: Discussionsupporting
confidence: 58%
“…DNA based molecular markers have been identified as powerful tools in assessment of genetic relationship among rice varieties due to their highly informative nature in revealing polymorphism compared to other markers (Neeraja et al 2006;Ashfaq and Khan 2012). The high number of polymorphic loci that can be otained through SSR markers has empowered them over AFLP markers and enables them to provide more specific informations (Jianming et al 2006;Wang et al 2013). However, the results from the study carried out by Spada et al (2004) shows that AFLP and SSR markers have been successfully used to analyse the genetic diversity of two varieties of Italian rice.…”
Section: Discussionmentioning
confidence: 99%
“…A great amount of useful information for genetic characterization and identification of poplars has accumulated, coming from the use of both allozyme polymorphism [28,30] or DNA markers: RAPDs [4,23,29,31] AFLPs, [1,6,8,15,40], microsatellites (SSRs) [3,6,10,14,30] and ISSRs [20].…”
Section: Introductionmentioning
confidence: 99%